Characteristics and application of fish oil-in-water pickering emulsions structured with tea water-insoluble proteins/κ-carrageenan complexes. (May 2021) - Ren, Zhongyang; Li, Zhanming; Chen, Zhongzheng; Zhang, Yuanyuan; Lin, Xiaorong; Weng, Wuyin; Yang, Hongshun; Li, Bin
Abstract: Food-grade Pickering emulsions (PEs) stabilized by proteins and polysaccharides have enormous application potential for preparing oil gels. Tea water-insoluble protein (TWIP) and κ-carrageenan (KC) were applied to prepare fish oil-in-water PEs and fish oil gels to broaden the application of fish oils at different ratios of TWIPs and KC. The turbidity reduced, but particle size unchanged except that of TWIP/KC mixture at 80:20 and zeta potential was not altered with the addition of KC. The β-turn and random coil of TWIPs were transformed into β-sheet, α-helix and β-antiparallel due to the addition of KC. Besides, TWIPs clustered with the increase of KC content, especially at 80:20. The droplets of the PEs stabilized by TWIP/KC mixtures were relatively small and homogeneous and the viscoelastic behavior of them was improved compared with those stabilized by TWIPs only. Finally, fish oil gels prepared using PEs stabilized by TWIP/KC mixtures had solid-like behavior with a storage modulus of almost 200 kPa. Therefore, TWIP/KC mixtures can be applied to prepare stable PEs and fish oil gels utilizing PEs as templates. These findings will help explore new edible materials, construct novel colloid structures of underused edible materials and their eventual use in real food manufacture. Graphical abstract: Image 1 Highlights: The κ-carrageenan (KC) reduced β-turn and random coil of tea water-insoluble proteins (TWIPs). Fish oil-in-water Pickering emulsions (PE) were prepared via TWIP/KC mixtures. Droplets of PE stabilized by TWIP/KC mixtures were reduced due to KC addition. PE stabilized by TWIP/KC mixtures could be as the template of fish oil gels. Fish oil gels stabilized by TWIP/KC mixtures had the solid-like behavior.